Impact of outflow from the Guadiana River on the distribution of suspended particulate matter and nutrients in the adjacent coastal zone - Cravo, Alexandra (2020)
In this study we collected surface water samples from the coastal area adjacent to the Guadiana estuary during winter for 3 consecutive years to assess the impact of the Guadiana outflow upon the concentration and spatial distribution of suspended particulate matter and nutrients (nitrate, phosphate, and silicate). Deeper water samples were also collected near the river mouth in water greater than 10 m in depth. Our results indicate that the maximal surface influence of the Guadiana outflow is close to the mouth of the Guadiana River, at the 10-m isobath, where the highest concentrations of suspended particulate matter (SPM) and nutrients were recorded, as well as the lowest salinity. SPM and nutrient concentrations decrease with increased water depth, while salinity increased. Beyond the 10-m isobath, toward the ocean, nutrient concentrations decreased gradually with increasing salinity. Nutrient concentrations showed a conservative behaviour only during the last of the three sampling periods. The impact of Guadiana outflow was especially low when river discharge was low, however, after periods of peak rainfall the river outflow increased enormously and the impact of SPM and nutrients (more than an order of magnitude higher than normal) was observed, particularly around the mouth of the estuary. This impact involved the development of a fingerprint plume that represents a net export of SPM and nutrients to the coastal area. This plume had a width of about 10e15 km, and despite being centred slightly east of the mouth of the Guadiana River, tended to migrate westward. The increase in N compounds was more significant than increases in P and Si, is reflected in high N:P and N:Si nutrient ratios. In water depths in excess of 10 m, the effect of the Guadiana outflow was most evident until 5 m depth. It is expected that with the completion of the biggest dam in Europe along the Guadiana River, the outflow of the river will be markedly reduced, especially during summer if climatic change continues to produce significant periods of dry weather. Under such conditions, nutrient concentrations will be reduced even further and impart a negative impact on nutrient biogeochemical cycles and productivity of the coastal zone.